3D printing of reinforced concrete elements: Technology and design approach. (20th March 2018) - Asprone, Domenico; Auricchio, Ferdinando; Menna, Costantino; Mercuri, Valentina
Highlights: We present the fabrication of RC members based on concrete 3D printing technology. A straight 3.00 m long RC beam is manufactured and tested under 3-point bending. A second RC beam has been also 3D printed with variable cross section. The approach will facilitate the production of free-form structurally optimized RC structures. Abstract: This paper deals with a novel approach to the fabrication of reinforced concrete (RC) members based on Concrete 3D printing technology. The approach consists in the partition of a RC member into different concrete segments printed separately and, then, assembled into a unique element along with the steel reinforcement system. The approach is expected to facilitate the production of free-form structurally optimized RC elements with the final aim of saving concrete material and, at the same time, fabricating lighter structures. As case study, we report on the material characterization and fabrication steps of a straight 3.00 m long RC beam together with the results of a full-scale three-point bending test performed on it. As a demonstration of the potentialities of this approach, the fabrication of a free-form variable cross-section RC beam is also presented.